Tert‑butyl catechol/alkaline‑treated kenaf/jute polyethylene hybrid composites: impact on physico‑mechanical, thermal and morphological properties - Md Rezaur, Rahman; Sinin, Bin Hamdan; Jayamani, Elammaran; Kakar, Akshay; Muhammad Khusairy, Bin Bakri; Fahmi Asyadi, Bin Md Yusof (Springer Nature Publishing, 2019)
.This study focuses on the efects of fber treatment on the mechanical, morphological, physical and thermal properties of kenaf/jute/polyethylene composites, by using alkaline-treated and raw fbers. The core of jute and kenaf fbers was chopped into shorter lengths and used for composite fabrication. The composites were then subjected to tensile, water absorption, SEM, FTIR, DSC and TGA tests. According to the FTIR spectroscopy results, the alkaline treatment removed a signifcant amount of lignin and other impurities, especially at lower infrared band. This reduced fbers’ hydrophilicity, making it more compatible with the polymer. This is evident from the SEM results, as it shows improved interfacial bonding. Therefore, the treated fber composites, especially for 15 wt% composites, have higher tensile strengths, more thermal stability and higher activation energy.